From Leviathan to Toro of Wall Street - Luque Baena, Enrique (Revista de Antropología Social, 2011)
What is nowadays the main antagonist to the great Hobbesian metaphor? In Jakobsian terms, the Bull of Wall Street seems to be much closer to the metonymical pole than to the metaphorical one. Somebody have equated the famous bull to Leviathan in a dual sense: first, since it has come to represent the empowerment of economy, the strength of the internal recovery phase of the stock market after periodic turmoils, just as Leviathan represented both the state autonomy and its political independece from church control; and, secondly, because if the Leviathan State eventually acquired sacred attributes, the Bull has come too to be identified with the stock market and ending up beeing equally revered.